188 Racial Disparities in Sleep During the COVID-19 Pandemic. (3rd May 2021) - Harra, Ryan; Snyder, Hope; Thurmon, Casey; Hire, Veronica; Walker, Jamie; Vargas, Ivan
Abstract: Introduction: The purpose of the present study was to estimate average sleep duration and sleep disturbance in the United States during the COVID-19 pandemic. In addition, we investigated whether sleep varied as a function of sociodemographic variables, in particular race. Long standing disparities in condition and available resources between racial demographics often lead to disparities in health. At the advent of a pandemic, which strains these systems further, it is important to assess whether or not racial disparities persist. This is important given that racial groups are likely affected by the pandemic, both directly and indirectly, in various ways. Here, we plan to at least assess whether there are any disparities with regard to sleep. Methods: 4, 048 adults (Mage = 45.8 years; 79% women) completed an online survey during April – June 2020. The final sample's self-reported race/ethnicity consisted of 84% White, 5.1% Black, 3.4% LatinX, 4.2% Asian or Asian American, and 2.9% Multi-racial. Sleep disturbance was assessed using a retrospective sleep diary and the Insomnia Severity Index (ISI). Results: Average sleep duration in the sample was 7.1 hours. Participants reported taking on average 32 minutes (SD = 38 mins) to fall asleep and reported waking up for 32 minutes (SD = 53 mins) during the night. Approximately 17% of the sample endorsed clinically elevated insomnia symptoms (based on the ISI ≥ 15 cut-off). With regard to racial differences, shorter total sleep time (TST), longer sleep latencies (SL), and greater total ISI scores were observed in Black (mean TST = 6.4 hours; SL = 37.7 minutes; ISI Total = 9.8) and LatinX (mean TST = 6.9 hours; SL = 37.1 minutes; ISI Total = 9.6) participants relative to White participants (Mean TST = 7.1 hours; SL = 30.9 minutes; ISI Total = 8.4). All p's < 0.05. Conclusion: Sociodemographic variables, particularly race, should be considered when estimating the relative impact of sleep on overall health. These findings are significant as they may have implications for a number of health disparities observed in the United States, especially during the COVID-19 pandemic. Support (if any): Vargas: K23HL141581